Independent role of interleukin-6 and interleukin-8 in the etiology of transfusion reactions to platelet concentrates in children - Šerbić Nonković, Olivera Miloš; Kuzmanović, Miloš; Životić, Maja; Žunić, Svetlana; Jovičić Gojkov, Dragana; Vujić, Dragana (Vojnosanitetski pregled, 2020)
Summary Background/Aim. Transfusion reaction is an adverse event which manifests during or after administration of blood components to the patient. We aimed to show less known aspects of most common transfusion reactions (allergic and febrile non-hemolytic transfusion reactions – FNHTR) in the pediatric population at the platelet concentrates. The aim of this study was to determine the role of the accumulated cytokines interleukin-6 (IL-6), interlekin-8 (IL-8) and presence of anti-platelet antibodies in the etiology of transfusion reaction in children. Methods. The study included 239 pediatric patients, who received platelet concentrates. Data of reported transfusion reaction were collected and evaluated prospectively. The levels of IL-6 and IL-8 were determined using an immunoassay. Anti-human leukocyte antigen antibodies (anti-HLA) and anti-human platelet antigen antibodies (anti-HPA) were identified by Luminex flow cytometry. Results. Toral of 70 transfusion reactions were recorded 52 patients. Allergic reactions occurred in most of the cases (74.3%), followed by FNHTR (17.1%). Platelets derived from buffy coat caused the majority of reactions (73.5%). Patients with infection after platelet transfusion with FNHTR had the highest levels of IL-6, 483.30 ± 1,041.79 pg/mL (p = 0.020). Respectively, the febrile patients had IL-6, 302.52 ± 720.04 pg/mL (p = 0.004). The level of IL-8 in platelet units that caused transfusion reactions was 95.66 ± 319.10 pg/mL, which was significantly higher (p = 0.001) compared to the control platelet units. Conclusion. The predominant etiologic mechanism for FNHTR in our study was leukocyte derived cytokine accumulation during storage. Etiopathogenesis of FNHTR induced by IL-6 and IL-8 presented differently. We concluded that significant factors in the etiology of FNHTR by IL-6 were the factors related to the pediatric patient (infection, inflammation).